Strategi Pemasaran Minyak Kemiri Bakar pada CV Amertha Sedana Sari di Denpasar - FEBRIANTI, ALFIN DWI; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Marketing Strategy of Roasted Candlenut Oil at CV Amertha Sedana Sari in Denpasar. CV Amertha Sedana Sari offers roasted candlenut oil products made from selected natural ingredients and without chemicals. This company has been able to create competitive advantages in products, services, prices and brand image in an effort to attract consumers, market attention and competition in business. Many factors influence it, both internal factors and external factors. This study aims to identify internal factors and external factors owned by the CV Amertha Sedana Sari in doing marketing and later determining alternative marketing strategies for roasted candlenut oil products. Analysis of the data used is the analysis of the IFAS Matrix, EFAS Matrix, and SWOT Matrix. The result of the research shows that there are four strength factors and three weakness factors in the internal. While the external factors there are four opportunity factors and three threat factors. The results of the calculation of the IFAS and EFAS matrices show that CV Amertha Sedana Sari in the SWOT matrix is in Quadrant 1 (2.86:3.261), The strategy applied is the S-O strategy, namely aggressive growth (Growth Oriented Strategy). It is hoped that CV Amertha Sedana Sari will maintain product quality for market expansion and utilize digital marketing in increasing marketing and increasing cooperation with farmers and product distribution facilities and infrastructure.